2016
DOI: 10.1038/srep34646
|View full text |Cite
|
Sign up to set email alerts
|

The trafficking of bacterial type rhodopsins into the Chlamydomonas eyespot and flagella is IFT mediated

Abstract: The bacterial type rhodopsins are present in all the three domains of life. In contrast to the animal type rhodopsin that performs mainly sensory functions in higher eukaryotes, the bacterial type rhodopsin could function as ion channel, pumps and as sensory proteins. The functioning of rhodopsin in higher eukaryotes requires the transport of rhodopsin from its site of synthesis to the ciliated outer segment of the photoreceptive cells. However, the trafficking of bacterial type rhodopsin from its site of synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 65 publications
3
31
0
Order By: Relevance
“…The availability of clean disruption mutants allowed us to quantify the relative contribution of ChR1 and ChR2, which is ;100:1 in CC-3404 gametes. The mislocalization of ChR1 after tagging with mCherry ( Figure 4D) suggests that an undisturbed C terminus is necessary for its targeting and/or transport to the eyespot along the four-membered microtubule rootlet (D4) (Mittelmeier et al, 2011;Awasthi et al, 2016). Using the ChR1 and ChR2 mutants, we determined that the ChR patch and eyespot globule layers can assemble independently.…”
Section: Channelrhodopsin Physiologymentioning
confidence: 99%
“…The availability of clean disruption mutants allowed us to quantify the relative contribution of ChR1 and ChR2, which is ;100:1 in CC-3404 gametes. The mislocalization of ChR1 after tagging with mCherry ( Figure 4D) suggests that an undisturbed C terminus is necessary for its targeting and/or transport to the eyespot along the four-membered microtubule rootlet (D4) (Mittelmeier et al, 2011;Awasthi et al, 2016). Using the ChR1 and ChR2 mutants, we determined that the ChR patch and eyespot globule layers can assemble independently.…”
Section: Channelrhodopsin Physiologymentioning
confidence: 99%
“…ChR1 and 2 are microbial rhodopsins that act as light-gated ion channels and absorb light mainly in the green and blue region of the visible spectrum to mediate phototaxis and photophobic responses (Nagel et al, 2002(Nagel et al, , 2003Sineshchekov et al, 2002;Govorunova et al, 2004). Recently, it was found that trafficking of these rhodopsins into the eyespot is even connected with the intraflagellar transport (Awasthi et al, 2016). Less is known about the His kinase rhodopsin HKR1, which is bimodally switched by absorbing UV-A and blue light, respectively, in vitro and has been suggested to mediate UV avoidance (Luck et al, 2012).…”
mentioning
confidence: 99%
“…Quantification of the fluorescence intensity at the eyespot and basal bodies showed approximately 50% of increase in the ChR2 signal intensity in dark cycle ( Figure 5B). The difference in the pattern of light dependent localization of ChR2 than that of ChR1, 25 indirectly validated the ChR2 specific signal in C. reinhardtii. Thus light was identified to play magnificent role in the differential localization pattern of ChR2 in Chlamydomonas.…”
Section: Light Affects the Localization Pattern Of Chr2 In Chlamydomonasmentioning
confidence: 63%
“…The cellular localization of the ChRs (photoreceptors) using antibody against ChR1 has been widely studied in Chlamydomonas. 14,17,19,25,27 However, the cellular distribution of ChR2 specifically, remained sparsely appraised. We identified the involvement of light as an important abiotic factor that influences the localization of ChR2 in Chlamydomonas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation